Job stress, job burnout and safety performance in the Palestinian construction industry. Issue 2 (3rd August 2015) - Enshassi, Adnan; El-Rayyes, Yasmine; Alkilani, Suhair
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purposes of this paper are to identify the most significant job-related stressors that influence construction project professionals' safety, identify the form of stresses and job burnout experienced by construction professionals and investigate the impact of stress and job burnout on safety performance from the perception of construction project professionals in the Gaza Strip construction industry. Construction is characterized as a stressful industry, which influences the safety performance of construction personnel, especially when the stress transfers into burnout. Design/methodology/approach – The views of a variety of construction professionals operating in Gaza Strip were sought using a questionnaire survey. Project managers, project coordinators and site engineers were targeted. Of the 45 questionnaires distributed, 33 were returned. Data were analyzed using the relative importance index (RII), Pearson correlation and regression analysis that used one-way ANOVA test. Findings – Findings revealed that an organizational stressor is the major contributor to physical stress, behavioral stress and job burnout. In addition, the findings showed that construction professionals suffered from emotional stress and invisible burnout. Of significance, the findings revealed that job stresses and job burnout did not affect safety performance in the Gaza Strip construction industry because the first priority for most construction professionals was to maintain permanent employment and, therefore, stresses were often hidden. Research limitations/implications – This study is limited by its small sample size. However, the findings represent novel results, which can be taken into consideration by construction organizations. Practical implications – The findings may help construction organizations in the Gaza Strip to understand job stressors' factors, which affect construction project professionals to help minimize or eliminate their impact on safety performance and, hence, improve productivity in construction projects. Furthermore, the study promotes personnel health and safety and enhancement of the quality of work and construction workers' personal life. The recommendation of this study may also apply to other developing countries. Originality/value – The study contributes to the overall body of knowledge relevant to job stress and burnout in the construction industry of developing countries. It draws attention to the interrelationship between stressors, stresses, burnout and safety performance, and it illustrates a new form of burnout that is invisible burnout.